2017
DOI: 10.4103/0976-9668.210007
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Class 1 integron and genetic diversity of Acinetobacter baumannii isolated from medical centers in Kermanshah

Abstract: Background and Objective:Acinetobacter baumannii has emerged as an important pathogen in hospital and environment that can acquire transport element and antibiotic-resistant genes. The aim of this study was to determine the resistances to different antibiotics, frequency of Class 1 integron in A. baumannii and then molecular typing for A. baumannii isolated from Intensive Care Unit (ICU).Materials and Methods:A total of 100 isolates of A. baumannii were collected from patients admitted to hospitals in Kermansh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…In a study in Brazil, 80% of A. baumannii isolates from ICU environment and 80.4% of isolates from ICU patients at the same hospital were imipenem resistance [ 24 ]. Consistent with the present study, in other studies conducted in Iran and Asian countries, the majority of A. baumannii isolates from clinical and environmental samples in ICUs were MDR, and resistance to carbapenems has been reported with high frequency [ 10 , 29 ]. Likewise, all studied strains of A. baumannii were sensitive to colistin, and tigecycline.…”
Section: Discussionsupporting
confidence: 92%
“…In a study in Brazil, 80% of A. baumannii isolates from ICU environment and 80.4% of isolates from ICU patients at the same hospital were imipenem resistance [ 24 ]. Consistent with the present study, in other studies conducted in Iran and Asian countries, the majority of A. baumannii isolates from clinical and environmental samples in ICUs were MDR, and resistance to carbapenems has been reported with high frequency [ 10 , 29 ]. Likewise, all studied strains of A. baumannii were sensitive to colistin, and tigecycline.…”
Section: Discussionsupporting
confidence: 92%
“…In a study in Kermanshah, Iran, in 2017, 50% of A. bommanii isolated from ICU were MDR and extensive drugresistant (XDR) (18). In a study in 2017 on BAL specimens from Babul, 47.9% of the specimens were A. baumannii, and 91.4% were MDR.…”
Section: Discussionmentioning
confidence: 99%
“…The current data showed that the resistance rate of imipenem (65.9%, Table 1 ) was higher than our previous report (60.9%) [ 10 ]. Although the resistance rate is lower than in Turkey (94.9%) [ 30 ] and Iran (82%) [ 31 ], it is still in a rising tendency. This suggests that carbapenems can’t be habitually used in A. baumannii infectious treatment.…”
Section: Discussionmentioning
confidence: 99%